Cytoxicity test of NaOCl and Mangosteen (Garcinia Mangostin L.) peel extract used as an irrigation solution in human periodontal ligament fibroblast cells (HPdLFc) - Tamara Yuanita; Dina Ristyawati; Karlina Samadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Root canal irrigation is an important stage in root canal treatment as it is requires to eliminate necrotic and debris tissue as well as root canal wetting. Unfortunately, root canal irrigation can cause the material utilised to pass into the apical foramen leading to periapical complications. Consequently, the irrigation solution should have low toxicity. Sodium hypochlorite (NaOCl) is a commonly used irrigation solution since it has antibacterial properties. Moreover, NaOCl is also known to have the ability to dissolve necrotic tissue, vital pulp tissue and organic components of dentin and biofilms. Nevertheless, it can still cause damage when coming into contact with periapical tissues. On the other hand, Mangosteen peel extract (Garcinia mangostana L.), also has antibacterial activities. Hence, Mangosteen peel extract is assumed to be employable as an alternative irrigation solution. Purpose: This research aimed to reveal the toxicity levels of NaOCl and Mangosteen peel extract (Garcinia mangostin L.) used as irrigation solution in human periodontal ligament fibroblast cells (HPdLFc). Methods: HPdLFc were obtained from periapical tissues taken from one third of the first premolar teeth cultured. These cells were subsequently divided into several groups exposed to NaOCl and Mangosteen peel extract at certain concentrations. A toxicity test was then conducted using MTT assay. The results were analyzed with an Elisa reader. Cell deaths and LC50 were then calculated. Results: NaOCl became toxic at a concentration of 0.254 µl/ml or 0.025%, while Mangosteen peel extract became so at one of 2.099 ug/ml or 0.209%. Conclusion: NaOCl can be toxic at a concentration of 0.254 µl/ml or 0.025% and Mangosteen peel extract at one of 2.099 μg/ml or 0.209%.